STRUCTRAL BEHA VIORE OF REINFORCED CONCRETE BEAMS STRENGTHED FOR SHEAR USING CFRP LAMINATES SUBJECTED TO CYCLIC LOADING - ABDEL WAHAB, LOUA Y MAHMOUD (2010)
The application of an external strengthening technique such as bonded fibrereinforced polymer (FRP) laminates seems to be an attractive technique to improve the structural behaviour of R.C elements under cyclic loading. FRP composite materials are widely employed because of their high strength to weight ratio, environmental resistance and ease of application over materials such as steel. In this research, an analytical model based on non-linear finite element algorithms coded in FORTRAN language was developed to enable the analysis of R.C beams externally strengthened for shear using CFRP laminates subjected to cyclic loads. 20-noded isoparametric quadrilateral elements with three degrees of freedom per each node were used to represent concrete. Material response is assumed to be orthotropic with tangent stiffness derived from stress-strain relationship for concrete under general biaxial state of stress. The reinforcement bars were represented in discrete manner. Three-dimensional space frame elements and space truss elements were used for this purpose. Material response is assumed to be elastic-perfectly plastic. 20-noded elements similar to those used to model concrete elements were used to represent CFRP side plates. Material response is assumed to be elastic-brittle. Discrete cracking approach was used to represent cracking. Primary consideration has been given to the representation of shear transfer mechanisms due to aggregate interlock in cracked concrete and dowel action in reinforcement. Expressions were derived from an analytical model in conjunction with experimental data to provide shear stress and stiffness values for special elements used to model aggregate interlock mechanism. A comparable approach was used to drive expression for dowel action mechanism. The bond-slip phenomenon between concrete and reinforcement was accounted for by using non-dimensional spnng elements. Shear stiffness values for such elements are obtained from expression based on experimental data. A new experimental methodology that enables to study the interfacial behaviour of CFRP-to-concrete joints under cyclic shear loading was developed. An experimental program consisted of testing specified number of push off specimens has been conducted. Mathematical formulation that govern the behaviour of the interface element was obtained, which are found in good agreement with the experimental results. This included the bond-slip behaviour, shear stiffness of interface and its degradation as number of cycle increased as well as the S-N curve. 3-d interface element is used to simulate this phenomenon. The element has sixteen nodes, eight nodes connect to concrete element and the other eight nodes connected to CFRP sheet. The interface was modelled by three linear springs connecting the joint nodes with the same coordinates. A computer program with combined-iterative method was used to solve the non-linear cyclic problem. A parametric analysis has been carried out to study the effect of controlling factors such as shear span-depth ratio, CFRP thickness on structural behaviour of R.C beams strengthened for shear with CFRP laminates subjected to monotonic or cyclic loading. The results from the analytical model were compared with corresponding experimental ones in order to confirm the validity of the analytical algorithm. The comparison between the analytical results and the published results gave a good agreement which indicates that experimental methodology proved to be appropriate and valid and that the analytical algorithm is quite efficient tool to study the structural behaviour of such element under cyclic loading as well as monotonic loading. Vll